Simulation of photodetector functionality in an optical communication system - Najafi, Mohammad Bahri (2010)
In the first experiment this thesis has studied the components of an optical communication system then after fully understand the characteristics of all optical systems we go to next step which is design and simulating the optical communication system and base of our knowledge the works begin to optimise both the individual components and also the entire optical system. The simulation results has been achieved by changing the characteristics of our communication system in the possible range and after that considering the improvements of observed results, then we tried to change other characteristics of the components to achieve the best optimum points. The charts and results are based on the observation from simulation and search in the latest articles and data sheets, and also calculation by the help of formulas extract from related books and literature. Finally after all the results achieved from simulation, calculation and literature that we have discussed in this project we can decide wisely about the components of any optical communication system to choose the best components base on the application and the circumstance which we want to work on it.